Dampak Rasio Keuangan Dan Pandemi COVID-19 Terhadap Kinerja Keuangan - Villy; Nuryasman MN (Jurnal Ekonomi, 2021)
This study has the purpose to determine the effect of ratios on financial performance by using current ratios, quick ratios, dan debt to assets ratios as measuring instruments for the dependent variable and using return on assets as measuring instruments for independent variables. The population of the financial statements is PT Multisport Indonesia for the 2019-2021 period. The sampling technique is purposive sampling. The analytical method to test the hypothesis is path analysis. Data processing using Eviews10 software. The result of the study found that the current ratio had a significant positive effect on return on assets, the quick ratio had a significant negative effect on return on assets,  and the debt on assets ratio had an insignificant negative effect on return on assets.